Sekolah sebagai Tempat Pesemaian Nilai Multikulturalisme - Anwar Efendi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
A nation’s reality showing cultural diversity, directed us to grasp multiculturalism principle. In this principle, there’s consciousness that nation is not singular, but plural, consist of many different components. Historical realities showing that Indonesian nation stand in midst cultural diversity. We can call Indonesia as most complete plural country in the world, beside America. In America, we know et pluribus unum slogan, resemble with bhineka tunggal ika, literally stand for many but one. Latest condition showed that cultural diversity became source of conflict between nations-components. Multidimensional crisis suffered by Indonesian nation still not ending yet. Therefore, we need explicit and clear action and step to maintain society’s attitude to care, respect, and understand cultural diversity values that become fundament of this nation and state. One of its steps is make cultural pluralism as educational strategy at school